Formulasi Sediaan Balsem dari Minyak Sereh sebagai Aromaterapi - Hamdan, Dian Furqani; Pasomba, Indiani (SIGn Journal of Public Health, 2023)
This study aims to make a balm formulation from lemongrass essential oil as aromatherapy and to find the results of a physical evaluation of a balm made from lemongrass essential oil. This research uses the experimental method. The research was conducted at the STIKES Bhakti Pertiwi Pharmacy Laboratory, Luwu Raya Palopo. Data obtained from observations and results of laboratory examinations were computerized and presented in tabular form with explanations. The results showed that the preparation of lemongrass leaf balm, which included organoleptic tests, homogeneous tests, pH similarity tests, and irritation tests, resulted in several conclusions. First, formula A, with a concentration of 15% citronella essential oil, meets the requirements for topical balm preparation. Second, formula B, containing 20% citronella essential oil, meets the requirements for topical balm preparation. Third, formula C with a concentration of 25% citronella essential oil does not meet the requirements for topical balm preparation because the preparation undergoes separation between solid and liquid preparations. Therefore, it is recommended for further research to focus on observing the concentration of 25% citronella essential oil so that it can be successfully used as a balsam preparation using laboratory equipment. That is more supportive or can be combined with other chemical substances to make it more homogeneous. In addition, further research is needed regarding more efficient packaging so that it can be easily used by patients, namely in the form of balm sticks, so that the general public likes the aroma of lemongrass. Furthermore, research is needed on the storability test of lemongrass balm formulations.